Dunia Moral dalam Permainan: Game Islam Digital dan Pembentukan Nilai-Nilai Anak Usia Dini di Ponorogo - Nurtina Irsad Rusdiani; Hera Yuantika; Sri Handayani (Lembaga Kajian dan Pemberdayaan Mahasiswa UIN Prof. KH. Saifuddin Zuhri Purwokerto, 2025)
Instilling Islamic moral values in early childhood is essential for lifelong character development. In today’s digital era, educational games offer an engaging way to foster these values. This study examines the use of digital educational games at BA Ronowijayan Siman Ponorogo to nurture Islamic morals in young children. Through classroom observation, teacher interviews, and document analysis, the research finds that digital tools—such as Islamic storytelling apps and interactive value-based games—significantly support the cultivation of honesty, responsibility, politeness, and devotion. Teachers play a crucial role by selecting suitable content and guiding children’s use of technology. The integration of digital media increases learning motivation and strengthens the internalization of Islamic values in everyday behavior. The study suggests ongoing development of Islamic digital learning resources and stresses the need for teacher training in educational technology for early childhood education